Supplement to The influence of changing seawater Ca concentration on Elements/Ca ratios in planktonic foraminifera: a culture experiment - AGU G3 - Le Houedec, Sandrine (Mendeley, 2020)
Table S1 and S2 : Data tables (S1 : elemental/Ca data and S2 : ANCOVA results) Table_culture : Resume table of planktic foraminifera G. siphonifera culture